ROLE OF GENETIC DIVERSITY FOR EXPLOITING THE HETEROSIS IN PIGEONPEA [CAJANUS CAJAN (L.) MILLSP.] - PRASAD, YOGENDRA; KUMAR, KAMLESHWAR; S. B. MISHRA (The Bioscan, 2013)
Fifteen pigeonpea genotype consisting of seven male parents, four male sterile and four maintainer were evaluated for 17 traits to quantify the genetic diversity existing among them by using Mahalanobis statistic. All the genotypes were grouped in to 4 clusters comprising the 4 genotype in each cluster except cluster-I having the 3 genotype only. The genotype placed in the one cluster either having the similar genetic background or belong to the similar geographical area. The maximum contribution towards divergence was observed by pollen viability test (41.90 %), followed by grain yield (29.52 %), 100-seed weight (10.48 %), grain/pods (5.71 %) and days to maturity as well as plant height contributed (2.86 %). Among all the crosses only three cross combination namely, ICP2043A/DA-11, H-28A/ MAL-28 and H-28A/IPA-203 have shown positive and significant standard heterosis for most of the yield and yield attributing traits, suggesting that these cross combination may be exploited to developed the hybrid using CGMS system in pigeonpea for obtaining higher grain yield owing to the diverse genetic back ground of the parental lines.